27. PULMONARY SCLEROSING PNEUMOCYTOMA: CASE REPORT (Vietnam Journal of Community Medicine, 2024)
Introduction: The issue at hand revolves around Pulmonary Sclerosing Pneumocytoma (PSP), a rare benign lung lesion predominantly found in Asian women. The rarity of this condition and its vague clinical characteristics pose challenges in the diagnostic process.Objective: This article aims to comprehensively report a case of PSP, providing an evaluation of imaging diagnostics, biopsy, and surgical intervention. The primary goals include contributing to scientific data, as well as sharing insights into the diagnostic and treatment processes.Case Report: A 36-year-old female patient was incidentally discovered to have a left lung mass during a routine health examination. The diagnostic approach involved CT, PET/CT, core biopsy, and video-assisted thoracoscopic surgery for tumor resection. Immunohistochemical staining of the tissue confirmed the distinctive features of PSP.Discussion: The discussion centers on the diagnostic characteristics of PSP, the challenges in distinguishing it from malignant lesions, and the strategic considerations for surgical intervention. Emphasis is placed on the rarity of PSP and underscores the significance of accurate diagnosis.Conclusion: Summarizing insights from the case report and discussion, the conclusion underscores the critical importance of precise diagnosis and effective treatment strategies for PSP. Encouragement is given for further research and long-term monitoring to deepen our understanding of this uncommon pathology.
Keywords: Pulmonary sclerosing pneumocytoma, pulmonary sclerosing hemangioma.